(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Mazkur maqolada Aleksandr Faynberg asarlarida sevgi mavzusi va inson qalbining ichki kechinmalari badiiy tahlil qilinadi. Shoir she’riyatida sevgi nafaqat romantik tuyg‘u, balki ma’naviy poklanish va ruhiy yuksalish omili sifatida talqin etiladi. Inson qalbining nozik holatlari, iztiroblari va umidlari poetik vositalar orqali yoritiladi. This article analyzes the theme of love and the inner experiences of the human heart in the works of Aleksandr Faynberg. In his poetry, love is interpreted not only as a romantic feeling but also as a source of spiritual purification and moral elevation. The delicate emotional states, sufferings, and hopes of the human soul are revealed through poetic devices.